Design Aplikasi Penjualan Tiket Hotel dengan Menggunakan Point of Sales pada Pesona Beach Inn Hotel - Ni Kadek Elisa Trisna Jayanti; I Gede Putu Krisna Juliharta; I Gusti Ayu Agung Istri Sari Dewi (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2020)
This research was conducted to hotel ticket sales application design using point of sales at Pesona Beach Inn Hotel. The data collection technique used in this research is qualitative research methods and descriptive methods, in the form of interviews and direct observation to find out the problems and needs of the hotel. The application design method uses an object based diagram approach with a tools in the form of a Flowchart Data Flow Diagram (DFD) and Entity Relationship Diagram (ERD). Due to hotel operational activities that are still carried out manually so that the services provided by the hotel are not fast enought and the recording is carried out repeatedly causing activities to be ineffective, then created a hotel ticket sales application design using point of sales. The hotel ticket sales application design using point of sales aims to help reservation activities, record data, calculate cost, and create reports that are still done manually, to be faster and more effective. The hotel ticket sales application design using point of sales at Pesona Beach Inn Hotel uses the PHP programming language with the Code Igniter framework and MySQL database.